CORRUPTION AND STOCK MARKET PERFORMANCE IN NIGERIA - Omodero, Cordelia Onyinyechi (Annals of Spiru Haret University. Economic Series, 2018)
Abstract The study examines the effect of corruption (using corruption perception index and Nigeria corruption ranking as proxies) on the stock market performance (proxied with share price index) in Nigeria. The study employed time series data spanning twenty years (1996-2016). Data availability especially on corruption indices was the major reason underlying the choice of period. The data were obtained from CBN Statistical Bulletin and Transparency International website. With the aid of SPSS version 20, the study used Multi-regression analysis and student t-test for the test of hypotheses. The study finds a significant positive correlation between corruption and stock market performance in Nigeria. The result reveals robust positive and significant relationships between Nigeria Corruption Ranking, Corruption perception index and Share price index. The result of the study explains the integration of graft into the Nigerian economic system. Therefore, adoption of a strong form of stock market efficiency by the Security and Exchange Commission (SEC) and Nigerian Stock Exchange (NSE) for actualization by all listed firms in Nigeria is hereby recommended. In addition, we recommend that the Federal and State governments should formulate more result-oriented policies and rules that could help combat corruption more effectively.